Musculoskeletal Pain With Body Mass Index, Duration of Activity and Lecture During Distance Learning - Caroline Costrila; Octavia Dwi Wahyuni (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Musculoskeletal disorders can be affected by a person’s body mass index, age, gender, duration of doing physical activities, duration of working or studying, ergonomics and body posture. The purpose of this study was to determine the relationship between musculoskeletal pain and its risk factors in the Faculty of Medicine of Tarumanagara University students during the long-distance study. This research is analytic with a cross-sectional study design. The research subjects were 303 subjects with an age range of 19–23 years using non-probability sampling. Musculoskeletal disorder levels were measured using the Nordic Body Map (NBM) questionnaire. The data obtained were analyzed using chi-square. The results obtained on musculoskeletal disorders with BMI had P= 0,473 (PRR= 1,213), musculoskeletal disorders with a duration of physical activity had 0,278 (PRR= 1,337) and musculoskeletal disorders with a duration of lectures had P=0,454 (PRR= 1,371). The results showed that there was no significant change between musculoskeletal disorders and BMI, duration of physical activity and duration of lectures in the Faculty of Medicine of Tarumanagara University students.